Study on chitosan thin film for vapour sensor application - Laheew, Abdulmula Salem Z.; Ahmed, Essia Ries; Tuty Fareyhynn Mohammed Fitri (School of Materials Engineering, 2012)
In this project, the different chitosan concentrations have been used to study the effect of chitosan concentrations towards the electrical properties of the chitosan films. At first, this study was focused on fabrication of chitosan film sensor then the electrical properties of the chitosan films. The last part of this study was the characterization of the microstructure of chitosan film. The chitosan films have been produced using an electrochemical deposition method. The chitosan films have been used to study the effect of the chitosan concentration on the performance of chitosan film sensor, whereas the study of the microstructure of the chitosan films were carried out using Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM) and Fourier Transform Infrared (FTIR). The performance of the chitosan films sensor was tested based on its stability to maintain its condition when exposed at different analyte to fulfill the requirement as a reliable sensor, all sensing properties i.e. Sensitivity, response time, stability, recovery, repeatability and selectivity of the chitosan film sensor towards water, methanol and toluene have been studied.